Tiger Tiger - Lambert, Jonny (Wilton, CT : Tiger Tales, 2017)
Old Tiger is left in charge of Cub, and Cub wants to play.
Keywords: Tiger -- Juvenile fiction; Tiger cubs -- Juvenile fiction; Jungle animals -- Juvenile fiction; Play -- Juvenile fiction; Tiger -- Fiction; Tiger cubs -- Fiction; Jungle animals -- Fiction; Play -- Fiction; Stories in rhyme